2012
DOI: 10.1038/ijir.2012.32
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of testosterone enanthate and tadalafil on PDE5 inhibitor non-reponders with severe and intermediate testosterone deficiency

Abstract: Several studies have suggested combination therapy with testosterone supplementation in patients not responding to PDE5 inhibitors. Considering the pathophysiological basis for testosterone supplementation, the present study aims to identify whether combination therapy allows persistence of treatment effect after testosterone discontinuation. Furthermore, we evaluated whether the degree of testosterone depletion affects treatment outcome from combination therapy. Hypogonadal patients (<350 ng dl(-1)) with erec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The findings of this integrated analysis challenge earlier reports that suggest normalizing testosterone levels is essential towards achieving a response to PDE5i therapy in men with low TT levels [14,1618,2023]. Our analysis corroborates and extends earlier reports that support that low androgen levels do not compromise PDE5i efficacy [24,32].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of this integrated analysis challenge earlier reports that suggest normalizing testosterone levels is essential towards achieving a response to PDE5i therapy in men with low TT levels [14,1618,2023]. Our analysis corroborates and extends earlier reports that support that low androgen levels do not compromise PDE5i efficacy [24,32].…”
Section: Discussionsupporting
confidence: 83%
“…Numerous reports suggest that erectile response to PDE5i is compromised in men with low TT levels [13–19] and that there is an improved response to PDE5i therapy in men with low TT levels following testosterone replacement therapy (TRT) [14,1623]. However, despite evidence supporting a possible link between low testosterone levels and reduced PDE5i efficacy for ED, a study in testosterone-deficient men not experiencing prior PDE5i failure suggests that TRT may not enhance the efficacy of PDE5i therapy [24].…”
Section: Introductionmentioning
confidence: 99%
“…The basic science literature has confirmed the necessity of androgens to generate adequate intracavernosal pressures and smooth muscle function to obtain an erection [59]. The literature showing the impact of testosterone replacement therapy (TRT) on erectile function is quite heterogenous (Table 1) [6061626364656667686970717273747576777879808182838485868788899091]. A subset analysis of the Olmstead County Cohort published by Gades et al [92] showed that testosterone has a statistically significant positive correlation with erectile function, even when adjusted for age.…”
Section: Hypogonadismmentioning
confidence: 99%
“…However, few clinical studies have been conducted in humans that evaluate the efficacy of combination therapy with testosterone and chronic PDE5Is. Kim et al [26] demonstrated that the combination of testosterone replacement and chronic PDE5Is was more beneficial to patients with severe testosterone deficiency. The patients received an intramuscular testosterone enanthate injection every 4 weeks for 12 weeks; they received a combination of testosterone enanthate injection and daily tadalafil 5 mg for the next 12 weeks.…”
Section: Figurementioning
confidence: 99%